2022-RA-727-ESGO Performance of the IOTA ADNEX model in differentiating between benign and malignant adnexal lesions in a Portuguese population. (20th October 2022) - Borges, André; Pinto, Patricia; Ambrósio, Paula; Condeço, Raquel; Martins, Ana; Passarinho, Rita; Bernardo, Maria José; Djokovic, Dusan
Abstract : Introduction/Background: The Assessment of Different NEoplasias in the adneXa (ADNEX) risk model was developed by clinicians and statisticians from the International Ovarian Tumor Analysis (IOTA) group to assist the diagnosis of ovarian cancer in patients who have at least one persistent adnexal tumor and are considered to require surgery. This study aimed to evaluate the diagnostic accuracy of the ADNEX model in 3 Portuguese tertiary referral centers. Methodology: The study was conducted between January 2016 and December 2020 and included consecutive non-pregnant ≥18-year-old patients with adnexal masses diagnosed at our units and submitted to surgery within 6 months after the ultrasound diagnosis. All scans were performed by IOTA-certified sonologists. The lesions were prospectively classified using the ADNEX model malignancy risk threshold set at ≥ 10%. By using the histological classification as the main outcome measure, the ADNEX sensitivity, specificity and accuracy were determined for malignant adnexa pathology and its subtypes. Results: This multicenter analysis involved 449 patients – 345 with benign and 104 with malignant lesions (35 borderline ovarian tumors [BOT], 25 stage I, 37 stage II – IV primary ovarian cancer and 7 secondary metastatic cancer to the ovary). Sensitivity, specificity and accuracy of the ADNEX model (with known CA-125 level in all cases) are shown in the accompanying table for global adnexal malignancy and specific subtypes. Regarding the frequent misclassified lesions, cystadenoma and cystadenofibroma were the most common histological entities misinterpreted as BOT (39/56), while 5/10 misinterpreted BOTs were considered invasive malignancies and another 5/10 benign lesions. Only 2/8 metastatic lesions were correctly classified. Conclusion: According to our data, the ADNEX performance in the Portuguese population is similar to that in previously studied populations. It discriminates well between benign and malignant tumors and offers fair to good discrimination between four subtypes of ovarian malignancy.